The Relevance of Islam in Indonesian Politics: A Study of the Integration and Sustainability of the Role of the Muslim Ummah - Amirullah, Amirullah (Civiliza Publishing, 2023)
This research explains the dynamic perspective of Islam and politics in Indonesia. The relationship between Islam and the political situation in Indonesia is not always harmonious. Using qualitative methods through literature study, this research resulted in the conclusion that the indications of Islam and politics are two aspects that are integrated in its development which has never been interrupted from the previous period. The existence of Islam in Indonesia is largely determined by the conditions of goals established by the Muslim community itself through qualifications and political capacity with an insight into the intellectual formation of its people. The condition of Muslims today is indeed progressing, but as a political institution it has experienced a setback. Therefore, discussions on Islamic and political issues are increasingly felt as urgent by Muslims themselves. The engineering of the discussion and its implementation includes a contextual understanding of Islamic doctrine with the nation's political growth, a coaching system that can liberate the people from material and spiritual backwardness, as well as leadership that is not only charismatic, but also dedicated and professional.